Academic Resilience and Procrastination in Students Who Study While Working - Glenis Veronica Toripa; Arthur Huwae (Bisma The Journal of Counseling, 2023)
Students who work carry out multiple roles in their daily lives, on the one hand working and, on the other hand, having to carry out responsibilities in the lecture process. This dual role is difficult because it provides many challenges and requires good psychological resilience. Therefore, this study aims to determine the relationship between resilience and academic procrastination in students who study while working. This research belongs to the quantitative research with the Karl Pearson correlation design. The subjects involved in this study were 205 working students aged 17-25 and were selected using a non-probability snowball sampling technique. Data collection in the study was carried out using a psychological scale as a questionnaire, which will be distributed online via Google Forms. The data obtained in the study were then analyzed using the product moment correlational analysis technique from Karl Pearson to determine the relationship between resilience and academic procrastination. The data analysis process was carried out with the help of the IBM SPSS Statistics 21 for Windows program. The results of the data analysis show that the correlation coefficient is -0.021 with sig. = 0.382 (p>0.05), meaning there is no significant negative relationship between resilience and academic procrastination in students who study while working.